Identification of Novel Genomic Regions for Biofortification Traits Using an SNP Marker-Enriched Linkage Map in Wheat (Triticum aestivum L.) - Krishnappa, Gopalareddy; Rathan, Nagenahalli Dharmegowda; Sehgal, Deepmala; Ahlawat, Arvind Kumar; Singh, Santosh Kumar; Singh, Sumit Kumar; Shukla, Ram Bihari; Jaiswal, Jai Prakash; Solanki, Ishwar Singh; Singh, Gyanendra Pratap; Singh, Anju Mahendru (Frontiers in Nutrition, 2021)
Micronutrient and protein malnutrition are recognized amongst the major global health issues. Genetic biofortification is a cost-effective and sustainable strategy to tackle malnutrition. Genomic regions governing grain iron concentration (GFeC), grain zinc concentration (GZnC), grain protein content (GPC), and thousand kernel weight (TKW) were investigated in a set of 163 recombinant inbred lines (RILs) derived from a cross between a cultivated wheat variety WH542 and a synthetic derivative (Triticum dicoccon PI94624/Aegilops tauschii [409]//BCN). The RIL population was genotyped using 100 SSR and 736 SNP markers and phenotyped in six environments. The constructed genetic map had a total genetic length of 7057 cM. A total of 21 novel QTLs were identified on 13 chromosomes representing all three genomes of wheat. Trait-wise highest number of QTLs were identified for GPC (10 QTLs), followed by GZnC (6 QTLs), GFeC (3 QTLs), and TKW (2 QTLs). Four novel stable QTLs (QGFe.iari-7D.1, QGFe.iari-7D.2, QGPC.iari-7D.2 and QTkw.iari-7D) were identified in two or more environments. Two novel pleiotropic genomic regions falling between Xgwm350–AX-94958668 and Xwmc550–Xgwm350 on chromosome 7D harboring co-localized QTL governing two or more traits were also identified. The identified novel QTLs, particularly stable and co-localized QTLs, will be validated to estimate their effects in different genetic backgrounds for subsequent use in marker-assisted selection. Best QTL combinations were identified through the estimation of additive effects of the stable QTLs for GFeC, GZnC, and GPC. A total of 11 RILs (8 for GZnC and 3 for GPC) having favourable QTL combinations identified in the present study can be used as potential donors to develop bread wheat varieties with enhanced micronutrients and protein.